Nursing interventions based on the theory of syndrome differentiation in the treatment of herpes zoster (以辨证施护理论为导向的护理模式在带状疱疹中的应用) - MENG Haiyan (孟海燕); SHANG Dongmei (尚冬梅); YANG Qingyi (杨清伊); MA Ying (马颖); LI Jiayue (李佳玥) (中西医结合护理)
Herpes zoster, known as "snake sore", "waist sore" and "spider sore" in Traditional Chinese Medicine, seriously affects the quality of life and health status of patients. This paper reviews the application progress of Traditional Chinese Medicine and theory of syndrome differentiation in clinical nursing of herpes zoster in recent years, and provides reference for improvement of integrative treatment of herpes zoster. (带状疱疹属中医学“蛇缠疮”“缠腰火丹”“蜘蛛疮”范畴, 严重影响患者的生活质量及健康状态。本研究就以辨证施护理论为导向的护理模式在带状疱疹的应用现状进行综述, 旨在为进一步完善该病的中西医结合疗法提供参考。)